2020
DOI: 10.3390/ma13061294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ion Beam Etching on the Nanoscale Damage Precursor Evolution of Fused Silica

Abstract: Nanoscale laser damage precursors generated from fabrication have emerged as a new bottleneck that limits the laser damage resistance improvement of fused silica optics. In this paper, ion beam etching (IBE) technology is performed to investigate the evolutions of some nanoscale damage precursors (such as contamination and chemical structural defects) in different ion beam etched depths. Surface material structure analyses and laser damage resistance measurements are conducted. The results reveal that IBE has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…Изучение ПС кварцевого стекла методом спектроскопии комбинационного рассеяния показывает, что в результате бомбардировки ионами Ar + в ПС возникают деформированные мостики Si−O−Si с напряженными связями. Эти связи образуют структурные кольцевые образования: пик D1 -490 сm −1 и пик D2 -605 сm −1 соответственно в 4-и 3-членных кольцевых структурах [59]. Относительные интенсивности пиков D1 и D2 первоначально увеличиваются, когда глубина травления ионным пучком составляет 50 nm, что свидетельствует об удалении грубых наноразмерных структурных дефектов в ПС и увеличении степени уплотнения по сравнению с исходной поверхностью.…”
Section: ионная полировкаunclassified
“…Изучение ПС кварцевого стекла методом спектроскопии комбинационного рассеяния показывает, что в результате бомбардировки ионами Ar + в ПС возникают деформированные мостики Si−O−Si с напряженными связями. Эти связи образуют структурные кольцевые образования: пик D1 -490 сm −1 и пик D2 -605 сm −1 соответственно в 4-и 3-членных кольцевых структурах [59]. Относительные интенсивности пиков D1 и D2 первоначально увеличиваются, когда глубина травления ионным пучком составляет 50 nm, что свидетельствует об удалении грубых наноразмерных структурных дефектов в ПС и увеличении степени уплотнения по сравнению с исходной поверхностью.…”
Section: ионная полировкаunclassified
“…For example, Ju et al demonstrated the laser damage degree on fused silica surface can be indicated through combining photothermal spectroscopy and optical microscope [24]. Zhong et al utilized photothermal spectroscopy to characterize nanoscale damage precursors on plasma-etched fused silica surfaces [25,26]. Despite these great efforts, the correlation between defects at various absorption levels and damage performance on fused silica surfaces is still not fully clarified due to the complexity of these absorbing defects.…”
Section: Introductionmentioning
confidence: 99%
“…Fused silica with high‐temperature resistance, chemical inertness, and outstanding transmittance from ultraviolet to infrared wavelength range is widely used in laser gyroscope, high‐power lasers, and ultraviolet lithography systems 1–4 . With the shortening of wavelength, the increase of power, and the improvement of system accuracy, it is urgent to achieve super smooth and defect‐free surface of fused silica to reduce optical scattering and loss as well as laser modulation, which are principally caused by surface defect and roughness 5–7 . It has been proved that the total integrated scatter of the optical component to be proportional to the square of the root‐mean‐square value of the surface roughness, 8–9 so the reduction of surface roughness is of great significance to improve the transmittance of optical components and the precision of optical imaging systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] With the shortening of wavelength, the increase of power, and the improvement of system accuracy, it is urgent to achieve super smooth and defect-free surface of fused silica to reduce optical scattering and loss as well as laser modulation, which are principally caused by surface defect and roughness. [5][6][7] It has been proved that the total integrated scatter of the optical component to be proportional to the square of the root-mean-square value of the surface roughness, [8][9] so the reduction of surface roughness is of great significance to improve the transmittance of optical components and the precision of optical imaging systems. Besides, surface defects can greatly reduce the laser-induced damage threshold of fused silica by weakening the mechanical properties, modulating the incident light field, and embedding absorptive impurities.…”
Section: Introductionmentioning
confidence: 99%